PENINGKATAN PENGETAHUAN PERPAJAKAN ATAS PENYESUAIAN PENGATURAN PAJAK PENGHASILAN UMKM N0 55 TAHUN 2022: PENDEKATAN SOSIALISASI DAN PENYULUHAN PADA UMKM BINAAN BUMDES MEDAL RAHAYU SUMEDANG - Frederica, Diana; Herianti, Eva Herianti; Mutiah, Mutiah; Susilawati, Susilawati; Nuryati, Tutty; Sapridin, Sapridin (UNIVERSITAS PGRI MADIUN, 2024)
Abstract. This research focuses on MSMEs (Micro, Small, and Medium Enterprises) that still lack an understanding of the importance of paying taxes and the comprehension of the tax regulations under PP No. 55 of 2022. The aim of the community service conducted by the Taxation Team of Accounting Lecturers from the Faculty of Economics and Business, who are part of the Forum of Accounting Lecturers in Higher Education in the DKI Jakarta region, is to carry out socialisation and education to improve the tax understanding of MSME actors partnered with Bumdes Medal Rahayu in Ambit Situraja Village, Sumedang, regarding the adjustment of MSME income tax regulations. In 2022, this Community Service activity, in the form of socialisation and education, was attended by 31 MSME actors fostered by Bumdes Medal Rahayu in Ambit Situraja Village, Sumedang. The socialisation and education were conducted by several speakers from the ABDIMAS taxation team. The community service method included lectures, discussions, practice, and Q&A sessions. The lecturers acted as speakers while the MSMEs were participants. Before explaining the tax material, participants were asked to complete a pre-test questionnaire. The results showed that out of the 31 MSME actors present, none understood how to report taxes, only 1 person knew how to calculate taxes and the tax rates for MSMEs, and 9 MSME actors had a Taxpayer Identification Number (NPWP). After the material presentation and Q&A session, participants were asked to fill out a post-test questionnaire. Based on the results of the activity, there was a significant improvement in participants' understanding of tax reporting, tax rates, and changes in tax regulations. Abstrak. Berfokus kepada UMKM (Usaha Mikro Kecil dan menengah) yang masih kurang memahami pentingnya UMKM membayar pajak dan pemahaman aturan perpajakan PP no 55 tahun 2022 yang masih kurang baik, maka tujuan dari pengabdian kepada masyarakat yang dilakukan tim perpajakan Dosen Prodi Akuntansi Fakultas Ekonomi dan Bisnis yang tergabung dalam Forum Dosen Akuntansi Perguruan Tinggi wilayah DKI Jakarta, yaitu melakukan sosialisasi dan penyuluhan Peningkatan pemahaman perpajakan pelaku UMKM Mitra Bumdes Medal Rahayu Desa Ambit Situraja Sumedang,atas penyesuaian pengaturan pajak penghasilan UMKM. Tahun 2022, Kegiatan Pengabdian kepada Masyarakat ini berupa sosialisasi dan penyuluhan, yang dihadiri oleh 31 pelaku UMKM binaan Mitra Bumdes Medal Rahayu Desa Ambit Situraja Sumedang. Sosialisasi dan Penyuluhan dilakukan oleh beberapa narasumber dari tim perpajakan ABDIMAS. Metode pengabdian kepada Masyarakat dalam bentuk ceramah, diskusi, Latihan dan tanya jawab.Dosen selaku narasumber sedangkan UMKM sebagai peserta,sebelum menjelaskan materi perpajakan peserta diminta menjawab kuisioner pre-test dengan hasil 31 orang pelaku UMKM yang hadir sebanyak 31 orang belum paham cara melaporkan pajak, 1 orang yang paham cara menghitung pajak dan mengetahui tarif pajak UMKM dan 9 pelaku UMKM yang memiliki NPWP. Setelah materi dan tanya jawab perserta diminta Kembali untuk mengisi kuisioner post-test berdasarkan hasil kegiatan Nampak perubahan signifikan pemahaman peserta mengenai pelaporan, tarif pajak dan perubahan aturan perpajakan.